Discovery and Mapping of the Triton Seep Site, Redondo Knoll: Fluid Flow and Microbial Colonization Within an Oxygen Minimum Zone - Wagner, Jamie K. S.; Smart, Clara; German, Christopher R. (Frontiers in Marine Science, 2020)
This paper examines a deep-water (~900 m) cold-seep discovered in a low oxygen environment ~30 km off the California coast in 2015 during an E/V Nautilus telepresence-enabled cruise. This Triton site was initially detected from bubble flares identified via shipboard multibeam sonar and which was then confirmed visually using the remotely operated vehicle (ROV) Hercules. High resolution mapping (to 1cm resolution) and co-registered imaging has provided us with a comprehensive site overview - both of the geologic setting and the extent of the associated microbial colonization. The Triton site represents an active cold-seep site where microbes can act as primary producers at the base of a chemosynthesis-driven food chain. But it is also located near the core of a local oxygen minimum zone, averaging <0.75 μM oxygen, which is significantly below average ocean levels (180-270 µM) and, indeed, extreme even among OMZs as a whole which are defined to occur at all oxygen concentrations <22µM. Extensive microbial mats, extending for >100m across the seafloor, dominate the site, whilst typical seep-endemic macrofauna were noticeably absent from our co-registered photographic and high resolution mapping surveys - especially when compared to all adjacent seep sites within the same California Borderlands region. This unusual discovery, in close proximity to Los Angeles, CA, provides an interesting natural laboratory for examining the biogeochemical and microbiological functioning of cold seep ecosystems within an Oxygen Minimum Zone. Current climate change predictions include possible expansion of OMZs, both up and down-slope along continental margins. Thus, study of the differences between cold seep communities within and shallower than the core of the current OMZ along the California Borderlands might provide important new insights into how cold seep communities might be expected to be impacted by future climate change along this and other continental margins.